Perenialisme dan Transformasi Pendidikan Karakter di Era Modern - Rohman, Taufikur; Khojir, Khojir; Soe’oed, Rahmad (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2023)
The objective of this research is to examine how perennialism addresses the challenges posed by the transition of moral education in the contemporary day, characterized by numerous instances of moral decline. This study employs a qualitative descriptive methodology, utilizing a literature review as the primary research technique. Perennialism posits ideas on the necessity for humans to acclimate and modify their behavior in response to shifts in the world. Character education, with the perennialism theory, focuses on how individuals conform to the inherent good principles inside themselves. Perennialism in character education emerged as a response to and remedy for the cultural turmoil in contemporary society. The concept of perennialism advocates for a return to the past by reinstating the enduring values and ideals that were deeply ingrained in ancient societies. Character education is a means to attain a reversion to the fundamental values and principles of life. To ensure the preservation of Indonesian identity in future generations, The Perennialism ideology is a viable option that should be implemented in character education. The findings of this research are anticipated to have a substantial impact on the formulation of enduring character education strategies, aimed at cultivating a generation that possesses not only academic proficiency but also a firm grounding in the esteemed principles of the nation and the teachings of Islam